Nature-based Solutions for Sustainable Urban Planning Greening Cities, Shaping Cities - Mahmoud, Israa H.; Morello, Eugenio; Lemes de Oliveira, Fabiano; Geneletti, Davide (Cham : Springer International Publishing : Imprint: Springer, 2022)
Urban greening policies and measures have recently shown a high potential impact on the design and reshaping of the built environment, especially in urban regeneration processes. This book provides insights on analytical methods, planning strategies and shared governance tools for successfully integrating Nature-Based Solutions (NBS) in the urban planning practice. The selected contributions present real-life application cases, in which the mainstreaming of NBS are investigated according to two main challenges: the planning and designing of physical and spatial integration of NBS in cities on one side, and the implementation of suitable shared governance models and co-creation pathways on the other. Chapter 5 is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. The authors have done an excellent job in presenting extremely comprehensive information and knowledge about NBS in a very simple and easy to understand way, even by non-experts. Congrats to them, the EU-funded projects that supported the research such as Horizon 2020 project Clever Cities. I hope the urban authorities and the professionals in the field will embrace it and use it in exercising their daily duties and tasks. Christos Fragakis, Policy Officer, Future Urban & Mobility Systems, EC (DG RTD).
Part I. Planning NBS in cities: insights and methods on spatial challenges -- 1. Nature-based solutions for resilient and thriving cities: Opportunities and challenges for planning future cities -- 2. Mainstreaming Nature-based Solutions in cities through performance-based planning: A case study in Trento, Italy -- 3. Insights for the enhancement of urban biodiversity using Nature-based solutions: The role of urban spaces in green infrastructures design -- 4. The environment-culture-technology nexus framework: an approach for assessing the challenges and opportunities for implementing nature-based solutions in Brazil -- Part II. Implementing NBS in cities: Case-study applications -- 5. Inclusive Urban Regeneration with Citizens and Stakeholders: from Living Labs to the URBiNAT CoP -- 6. Nature4Cities: Nature-based Solutions tools implementation within cities -- 7. The Implementation of Connectivity Area in the Metropolitan Region of Campinas (São Paulo, Brazil) -- 8. Analysis of Safety and security perception in Biblioteca degli Alberi (BAM) Park in Milan, Italy.
Keywords: Urban ecology (Biology).; Urban policy; Human ecology-Study and teaching; Sociology, Urban; Landscape architecture; Geography; Urban Ecology; Urban Policy; Environmental Studies; Urban Sociology; Landscape Architecture; Regional Geography